The status of youth coach training in the United States: Existing programs and room for improvement - Fawver, B.; Beatty, G. F.; Roman, J. T.; Kurtz, K. (International Sport Coaching Journal, 2020)
The United States is one of the world`s perennial sports powers, yet the pathway to that success is littered with millions of youth athletes who either are not good enough to compete at a higher level or dropout from sport completely due to various personal, social, and organizational factors. These barriers are compounded by a win-at-all-costs mentality that pervades the U.S. sport culture and ultimately disenfranchises many youths from the opportunity to enjoy sport participation throughout their life. The authors argue that principle components in this flawed system are the lack of standardized coach education at the state and national level, weaknesses in the current curricula offered, and difficulties for aspiring coaches accessing existing training programs. In the current paper, the authors (a) briefly review the history of coach education in the United States as well as existing opportunities for coach education at the university, sport-specific, and private sectors; (b) provide a description of the strengths and weaknesses of the current coaching model; and (c) provide recommendations to improve coach education and training in the United States.